2013
DOI: 10.1039/c3fo60346f
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meal composition on the release of fatty acids from salmon during in vitro gastrointestinal digestion

Abstract: We hypothesize that the rate of release of lipids from salmon muscle during in vitro digestion is altered by additional meal components. In vitro digestion of salmon was performed using a mixture of porcine gastrointestinal enzymes and bile salts. Broccoli and barley were also added to the digestion simulating a meal. The extent of lipolysis was determined by measuring the release of fatty acids (FAs) during sampling at the simulated gastric phase endpoint (60 minutes) and 20, 40, 60, 80, 110 and 140 minutes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Moreover, the food matrix also may impact on the release of FA during in vitro intestinal digestion. In this line, it has been shown that adding barley to a meal increases the release of long-chain PUFA and their percentage contribution to the total FA in the digest [ 60 ]. Therefore, the ingredients added to the whey beverage Colada , such as barley and Maracuyá polyphenols, could have contributed to increase the PUFA proportions in the BF after the in vitro digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the food matrix also may impact on the release of FA during in vitro intestinal digestion. In this line, it has been shown that adding barley to a meal increases the release of long-chain PUFA and their percentage contribution to the total FA in the digest [ 60 ]. Therefore, the ingredients added to the whey beverage Colada , such as barley and Maracuyá polyphenols, could have contributed to increase the PUFA proportions in the BF after the in vitro digestion.…”
Section: Resultsmentioning
confidence: 99%
“…The present study was based on a previous experiment where broccoli and SM were digested together, as in a meal, using a semi-dynamic in vitro digestion model. 1 The former experiment showed that broccoli inhibited the release of FA from SM during the rst 40 minutes of in vitro digestion, followed by a stimulation of the lipolytic activity. The following increase in lipolysis was suggested to be due to methodological issues related to performing in vitro lipolysis in a closed system, 1 whereas the initial inhibitory effect of broccoli was suggested to be due to lipase inhibition by polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…41 Our previous study showed that broccoli easily dispersed lipid droplets during digestion of SM. 1 The emulsi-cation properties may be partly due to the action of proteins and peptides that are well known to absorb to the oil-water interface. This hypothesis is only partly supported by data from the present study, showing a somewhat higher, although not signicant, increase in the release of FA from SM compared to SO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations